3-Dimensional graphene/Cu/Fe3O4 composites: Immobilized laccase electrodes for detecting bisphenol A. Issue 17 (16th September 2019) - Lou, Congqiang; Jing, Tao; Tian, Jingzhi; Zheng, Yongjie; Zhang, Jiaoxia; Dong, Mengyao; Wang, Chao; Hou, Chuanxin; Fan, Jincheng; Guo, Zhanhu
Abstract: Abstract : Three-dimensional graphene (3D-GN)/Cu/Fe3 O4 composite support materials were synthesized by a modified chemical reduction method using graphene oxide precursor. A 3D-GN/Cu/Fe3 O4 biosensor was prepared by coating the electrode with laccase. The electrochemical properties of the biosensor were investigated by cyclic voltammetry (CV) and differential pulse voltammetry using potassium ferricyanide, phosphate-buffered saline (PBS) solution, and bisphenol A (BPA) solution. The current response of 3D-GN/Cu/Fe3 O4 biosensors presents a remarkable sensitivity based on CV. The linear range of BPA is 7.2–18 μM using differential pulse voltammetry in PBS solution (pH= 4.0). A linear fitting equation of the laccase biosensor was observed for the current response as a function of BPA concentration. The detection limit was decreased to 1.7μ M. The detection approach herein turns out to be highly sensitive, has a wide linear range, and exhibits excellent stability.